Strategi meningkatkan akses dan layanan inklusif bagi pengguna disabilitas di perpustakaan - Geri, Cherin Afrianti; Mudawamah, Nita Siti (Daluang: Journal of Library and Information Science, 2025)
Purpose. This study analyses strategies, challenges, and obstacles in developing accessibility and services for visitors with disabilities at the Jakarta-Cikini Library. Methodology. A descriptive qualitative approach was employed using observations, interviews, and documentation. Informants were selected through purposive sampling and included staff from the service section and the Inclusion Room, as they are directly responsible for managing library services and inclusive facilities. Managing library services and the management of the Inclusion Room. Results and discussion. The findings show that the library implements several strategies to improve accessibility for people with disabilities. These include organising disability-related activities during specific events, promoting services through word-of-mouth and outreach to special education institutions, and utilising social media campaigns. The library also collaborates with disability organisations to procure assistive devices, develop accessible collections, and enhance staff competence. A disability-friendly environment has also been established within the library. However, several challenges remain, including limited innovation in promotional efforts, a shortage of competent human resources, and restricted space, tools, and collections. The library further encounters obstacles related to internal and external regulations affecting collaboration and building maintenance, as well as inadequate public facilities that hinder mobility for people with disabilities. Conclusions. The Jakarta-Cikini Library has undertaken multiple efforts to improve inclusive services through facility provision, staff capacity-building, targeted promotion, and partnerships with disability organisations, technology companies, and educational institutions. However, administrative barriers, limited resources, and insufficient supporting infrastructure remain significant obstacles to fully realising an accessible and inclusive library environment.